Expression of DOCK9 and DOCK11 Analyzed with Commercial Antibodies: Focus on Regulation of Mutually Exclusive First Exon Isoforms - Antonio Parrado (Antibodies, 2020)
Dedicators of cytokinesis 9 and 11 (DOCK9 and DOCK11) are members of the dedicator of cytokinesis protein family encoding the guanosine nucleotide exchange factors for Rho GTPases. Together with DOCK10, they constitute the DOCK-D or Zizimin subfamily. Two alternative full-length amino terminal isoforms of DOCK9 are known, which we will call DOCK9.1 and DOCK9.2. In order to investigate the relevance of the presence of the alternative first exon isoforms within this family, and to lay the groundwork for future studies that seek to investigate their potential role as biomarkers of disease, the expression levels of DOCK9 and DOCK11 were measured by qRT-PCR in 26 human tissues and 23 human cell lines, and by Western blot analysis, using commercial antibodies in cell lines. DOCK9.1 and DOCK9.2 were widely distributed. High levels of expression of both isoforms were found in the lungs, placenta, uterus, and thyroid gland. However, only DOCK9.1 was significantly expressed in the neural and hematopoietic tissues. The unique first exon form of DOCK11 was highly expressed in hematopoietic tissues, such as the peripheral blood leukocytes, spleen, thymus, or bone marrow, and in others such as the lungs, placenta, uterus, or thyroid gland. In contrast to tissues, the expression of DOCK9.1 and DOCK9.2 differed from one another and also from total DOCK9 in cell lines, suggesting that the amino terminal isoforms of DOCK9 may be differentially regulated. This study demonstrates the usefulness of antibodies in investigating the regulation of the expression of DOCK9.1, total DOCK9, and DOCK11.